Applications of the oral microbiome in personalized dentistry - Belibasakis, Georgios N.; Bostanci, Nagihan; Marsh, Philip D.; Zaura, Egija (Archives of oral biology, 2019)
•Dysbiotic changes of the oral microbiome may lead to disease.•Knowledge of the oral microbiome can be applied in personalized dentistry.•Personalized dentistry can reflect clinical application and individual populations.•Oral microbiological analysis can be performed at point-of-care hubs. In the era of personalized medicine, it is imperative that oral health is integrated into this concept. The oral cavity fosters a highly individualized microbiome that has evolved to promote oral health, and which exists in a dynamic balance with the host. Microecological changes to the biology of the mouth [e.g. in the host diet and lifestyle, or status of the immune system] may drive deleterious shifts in the composition or metabolic activity of the oral microbiome [‘dysbiosis’]. This review aims to explore how knowledge of the oral microbiome may be utilized for personalized dentistry at the point-of-care. This is a comprehensive narrative review of the literature, summarizing the perspectives of the authors. The huge increase in recent knowledge on the ecology and microbiology of the oral cavity generated by ‘OMIC’ technologies may indeed be clinically translated to support patient care, in terms of prevention, monitoring, risk classification or early diagnosis. The identified clinical applications may not only include dental caries and periodontal disease, but also dental implants and orthodontics. Population-based applications may include systemic health, pregnancy and elderly populations. Applications of selected oral microbiome and host-related biochemical parameters [e.g. the saliva proteome] for personalized dentistry can be customized for different clinical applications or individual populations, at point-of-care hubs.